النص المفتوح بين النقدين الغربي و العربي - عارف, سیڤا علي; أحمد, فائق مصطفى (Sulaimani Journal for Humanities, 2018)
This research is titled (The open text between western and eastern criticism), it is part of a doctoral thesis in Arabic literature under the title (Open texts in the works of Falakadin Kakaye). This research includes the theoretical topics related to and shed light on open texts, it is dedicated to the beginning and emerge of open texts; and later developments of the theory among the critics of the West, especially with the critic and theoretician Umberto Eco and the stages of evolving open text. We have later talked about the analysis and opinions of the western critics, and displayed the point of view of the Arab critics of the theory which might be different; especially in their focus on openness or open text by benefiting various techniques of different genres of literature and talking about the most important tools and their characteristics; in addition to referring to different types of the open texts, and at the end concluding various definitions and understandings of types of open texts.